Identification and biochemical characterization of p70TRK, product of the human TRK oncogene. - Mitra, G (1987)
TRK is a human transforming gene generated in a colon carcinoma by a somatic rearrangement that fused a nonmuscle tropomyosin gene to sequences that shared extensive homology with members of the tyrosine-protein kinase supergene family. These sequences are likely to be derived from a transmembrane receptor gene whose putative ligand binding domain has been replaced by tropomyosin. In the present studies, we have expressed the entire coding sequences of the TRK oncogene as well as its protein kinase-related carboxyl-terminal domain in Escherichia coli. Antisera raised against these bacteria-synthesized TRK polypeptides has allowed us to identify the gene product of the TRK oncogene as a 70-kDa protein. Immunoprecipitates containing p70TRK have an associated protein kinase activity specific for tyrosine residues. Moreover, p70TRK is phosphorylated in vivo in serine (75%), threonine (20%), and tyrosine (5%) residues. Finally, immunofluorescence and cellular fractionation studies indicate that p70TRK is preferentially located in the cytoplasmic fraction.